All you need is a love spell - Reisfeld, Randi (New York : Pocket Books, 1998)
Sabrina is not too concerned when the kids at school suddenly start pairing off, but she becomes alarmed when her Harvey seems to be falling for another girl and she is determined to find out what is going on.
"An Archway paperback.".
"Based on the hit TV series"--Cover.
7.6
3-6
Keywords: High school students -- Fiction; Magic -- Fiction; Witches -- Fiction; High school students -- Fiction; Magic -- Fiction; Witches -- Fiction